Comparison of the effects of valgus loading and internal axial tibial torque on ACL strain during a simulated jump landing. Issue 4 (27th March 2011) - Oh, Y; Ashton-Miller, J; Wojtys, E
Abstract : Background: Little is known about how much Anterior cruciate ligament (ACL) strain is increased by a valgus moment versus an internal axial tibial torque loading during a unipedal jump landing. Objective: To test the (null) hypothesis that the anteromedial (AM) bundle ACL relative strain would not be significantly different under a simulated one-foot jump landing imposing an internally-directed tibial torque versus one imposing a valgus knee moment. Design: 12 cadaveric knees (mean (SD) age: 65.0 (10.5) years) were tested to study the effect of internally-directed tibial torque on the AM-ACL relative strain. Pretensioned quadriceps, hamstring and gastrocnemius muscle-tendon unit forces maintained an initial knee flexion angle. A compound impulsive test load (2*BW compression, flexion moment and internal tibial torque or valgus knee moment) was applied to the tibia while recording the 3-D knee loads and tibofemoral kinematics. AM-ACL relative strain was measured using a 3 mm DVRT. Each loading condition (ie, 'internal' or 'valgus' loading) was compared against 'baseline' loading condition under compression and flexion moment. Results were compared with those from Withrow et al . (2005) for 11 cadaveric knees of similar age tested on the same apparatus to investigate the effect of valgus knee loading on AM-ACL relative strain. The Wilcoxon Signed-Rank test was used to test the null hypotheses (p<0.05 being considered significant). Setting: A cross-sectional, repeated measures, in vitro laboratory study. Assessment of risk factors: Independent variables included the magnitude of the impulsive compressive force, flexion moment, and internal tibial torque or valgus knee moment. Main outcome measurement: AM-ACL relative strain. Results: Normalised peak AM-ACL relative strain increased 117% under internally-directed tibial torque (17 ± 4 N-m), whereas the corresponding value increased 30% under valgus knee loading (133 ± 29 N-m) (p=0.016). Conclusion: Internal axial tibial torque increases AM-ACL relative strain more than a valgus load under a simulated jump landing.